2009
DOI: 10.2165/00003088-200948040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pharmacokinetics of Gentamicin in Preterm and Term Neonates

Abstract: Bodyweight and age (GA and PNA) were found to be major factors contributing to IIV in gentamicin clearance in neonates. Based on these data, cystatin C and serum creatinine were not correlated with gentamicin clearance and therefore not likely to be predictive markers of renal function in this patient population. Based on predictions from the developed model, preterm neonates do not reach targeted peak and trough gentamicin concentrations after a standard dosage regimen of 4 mg/kg given once daily, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 48 publications
9
73
2
6
Order By: Relevance
“…Our calculations extend two papers (8,9) on PK/PD modeling of neonatal gentamicin treatments. Figure 2 is a condensed summary.…”
Section: Deterministic and Stochastic Neonatal Gentamicin Pk/pd Modelingsupporting
confidence: 68%
See 1 more Smart Citation
“…Our calculations extend two papers (8,9) on PK/PD modeling of neonatal gentamicin treatments. Figure 2 is a condensed summary.…”
Section: Deterministic and Stochastic Neonatal Gentamicin Pk/pd Modelingsupporting
confidence: 68%
“…One PK/PD approach to modeling gentamicin treatment of E. coli in neonates is given in (8,9). The approach takes into account drug-induced "adaptive resistance," which is reversible within days [reviewed in (4,10)]; it does not consider irreversible resistance caused, e.g., by bacterial mutations (11,12).…”
Section: Pk/pd Modelingmentioning
confidence: 99%
“…Routine monitoring of the C peak is not indicated when gentamicin is administered once daily, as it is expected to reach levels above those when given twice daily. According to the references, therapeutic gentamicin concentration C peak is ranging from 15-25 mg/l, but it often exceeds 25 mg/l, which is not associated with adverse effects on clinical outcome [1,15]. However, concentrations below 15 mg/l could be linked with the potential inefficiency due to C peak :MIC ratio <8:1 [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, wide inter-individual variability was observed. In the study by Mannan et al, difference in the renal function between pre-and full-term neonates was explained by gestational age [9], while Nielsen et al showed that bodyweight, and both gestational and postnatal age were found to be main factors contributing to variability in gentamicin CL in neonates [15]. Furthermore, Knight et al, revealed significant difference between the mean trough concentrations assessed on day 2 versus days 3 or 4 [20].…”
Section: Discussionmentioning
confidence: 99%
“…The approach to dosing in newborns has been suggested to be based on their body weight, gestational age (GA), and postnatal age as these characteristics reflect the pharmacokinetics (PK) in this population (43). A three-compartment PK model of gentamicin disposition in preterm and term newborn infants was recently described based on a prospective study (35).…”
mentioning
confidence: 99%